The media’s framing of the Greek bailout referendum: A crisis-inducing or a crisis-resolving mechanism? - Milioni, Dimitra L.; Spyridou, Lia Paschalia; Triga, Vasiliki (My University, 2018)
After five years of economic and sociopolitical turmoil, the Greek coalition government, led by left-wing Syriza, announced the July 5 referendum, asking citizens to decide whether or not to adopt the EU-proposed economic plan. The decision for the referendum triggered severe criticisms and the media campaign became the ground for a struggle between competing narratives of the referendum. This paper examines the range of media frameworks that were employed to make sense of the referendum in the week between its announcement and the vote itself. The study shows how these different frameworks can be linked to the notion of crisis, which emerged as a crucial concept for the Greek bailout referendum.
Cadrages Médiatiques de la Consultation Grecque sur le Plan d'aide Européen: Le Référendum Cause ou Solution de la Crise
Keywords: referendum campaigns; framing analysis; Greek bailout referendum; crisis